(untitled) (Journal of the College of Basic Education, 2022)
This study was carried out in the green house of Biology Department, College of Education for Pure Science IbnAL–Haitham( Baghdad University), during the growing season of 2015,Experience has included study the effect of the concentrations of kinetin (25,50,75,100) mg/L with two level of NPKZn manure,It added level 160 Kg/H as well as the lack of added which is the control treatment, the effect of sodium chloride in two concentrations (50,100)mM/L and their interactions in concentration som major elements (nitrogen , phosphorus , potassium, magnesium , calcium experiment was conducted according to the design of Randomized Completely Block Design(RCBD). with three replications, the results confirmed the following: The existence of a significant decrease the impact of sodium chloride of the Soil in the rates of traits studied compared to the treatment of control and a significantly increased in the qualities mentioned above at spray plants with kinetin and fertilizing with NPKZn fertilizer, individually or their overlap and minimize the negative effect of sodium chloride. Focus (75) mg/L of kinetin was beating if given the best rates above mentioned qualities,with the superiority of treatment(the level160 Kg/H of manure and focus(75) mg/L of kinetin) was beating if given the best rates above mentioned qualities..